ALMA versus DDD - Cruz, Daniela (2008)
To be a debugger is a good thing! Since the very beginning of the programming activity, debuggers are the most important and widely used tools after editors and compilers; we completely recognize their importance for software development and testing. Debuggers work at machine level, after the compilation of the source program; they deal with assembly, or binary-code, and are mainly data structure inspectors. Alma is a program animator based on its abstract representation. The main idea is to show the algorithm being implemented by the program, independently from the language used to implement it. To say that ALMA is a debugger, with no value added, is not true! ALMA is a source code inspector but it deals with programming concepts instead of machine code. This makes possible to understand the source program at a conceptual level, and not only to fix run time errors. In this paper we compare our visualizer/animator system, ALMA, with one of the most well-known and used debuggers, the graphical version of GDB, the DDD program. The aim of the paper is twofold: the immediate objective is to prove that ALMA provides new features that are not usually offered by debuggers; the main contribution is to recall the concepts of debugger and animator, and clarify the role of both tools in the field of program understanding, or program comprehension.